2014
DOI: 10.1038/bmt.2014.281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IKZF1 deletions on long-term outcomes of allo-SCT following imatinib-based chemotherapy in adult Philadelphia chromosome-positive ALL

Abstract: We investigated the prognostic relevance of IKZF1 deletions in 118 adult Ph-positive ALL patients who had minimal residual disease (MRD) data under a uniform treatment of allo-SCT following first-line imatinib-based chemotherapy. IKZF1 deletions were identified in 93 patients (78.8%). IKZF1-deleted patients had a lower proportion of early-stable molecular responders compared with wild-type patients (28.0 vs 56.0%, P = 0.028). After a median follow-up of 72 months, IKZF1-deleted patients had a trend for higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…Thereby, only the presence CDKN2A/2B deletions but not IKZF1 deletions showed to be significantly adverse for all endpoints. On one side, this could possibly be attributed to the higher fraction of patients with IKZF-deletions, 75% in our cohort versus 50 % in the cohort of Kim et al 28 and as compared to the frequency of CDKN2A/2B deletions, which were more evenly distributed so that the prognostic value of IKZF1 deletions was weaker than that of CDKN2A/2B deletions.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Thereby, only the presence CDKN2A/2B deletions but not IKZF1 deletions showed to be significantly adverse for all endpoints. On one side, this could possibly be attributed to the higher fraction of patients with IKZF-deletions, 75% in our cohort versus 50 % in the cohort of Kim et al 28 and as compared to the frequency of CDKN2A/2B deletions, which were more evenly distributed so that the prognostic value of IKZF1 deletions was weaker than that of CDKN2A/2B deletions.…”
Section: Discussioncontrasting
confidence: 55%
“…27 Arguments possibly explaining an exceptionally strong role of CDKN2A/2B deletions in Ph+ ALL have been shown by functional biologic experiments indicating absence of gene expression from the CDKN2A/2B locus co-operates with the BCR-ABL oncogene to enhance the aggressiveness of the disease by strongly increasing the self-renewal capacity of leukemia cells, increasing clonal turnover and thereby conferring resistance to TKI therapy. [48][49][50] Furthermore, our results are also not in disagreement with the study by Kim et al 28 , where a negative impact of IKZF1 deletions was shown for relapse, which was however not retained in multivariable analysis. Furthermore, in that study, no comparison regarding the prognostic value of IKZF1 deletions in combination with other deletions was made because other lesions were not examined.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Copy number alterations identified by CMA in these cases are of prognostic significance. Deletion involving IKZF1 gene has been found to be associated with very poor prognosis in children and adversely affects treatment outcomes in both children and adult patients . Although findings are conflicting, patients with CDKN2A deletion deserve careful observation and management.…”
Section: Resultsmentioning
confidence: 99%